Reimagining rehabilitation: beyond the individual - Burke, Lol (Routledge, 2019)
Introduction: what's wrong with contemporary rehabilitation and why do we want to change it? -- Reimagining social control and support : current realities, dystopian futures? -- Reimagining the rehabilitative journey : personal rehabilitation -- Reimagining the legal and sentencing framework : judicial rehabilitation -- Reimagining practice cultures and values : moral rehabilitation -- Reimagining civil society and community engagement : social rehabilitation -- Conclusion: beyond the personal : reimagining something better, fairer and more effective?